2011
DOI: 10.1002/dc.21628
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the quality of smears in transbronchial fine‐needle aspirates using two staining methods for rapid on‐site evaluation

Abstract: Transbronchial needle aspiration (TBNA) via flexible bronchoscopy is a well-established sampling modality for lung masses. The procedure is useful in the diagnosis of neoplastic and non-neoplastic lesions as well as for staging of bronchogenic carcinoma. Rapid on-site evaluation (ROSE) adds value as it has the advantage of triaging material during the procedure so avoiding a battery of investigations. Frequently used rapid stains are the modified Wright-Giemsa water-based stain (WG-ROSE) and the alcohol-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 14 publications
0
11
0
1
Order By: Relevance
“…One study [44] suggested that the less costly and labor-intensive method of Wright-Giemsa staining for ROSE provided equivalent diagnostic and quality performance compared to Papanicolaou staining. Another study [42] suggested that liquid-based cytology was resource saving in that only 1 slide required preparing and examination (compared to 7 for Papanicolaou staining), and that pathology reporting time may be reduced by up to 20 min per case.…”
Section: Results Of Pico Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study [44] suggested that the less costly and labor-intensive method of Wright-Giemsa staining for ROSE provided equivalent diagnostic and quality performance compared to Papanicolaou staining. Another study [42] suggested that liquid-based cytology was resource saving in that only 1 slide required preparing and examination (compared to 7 for Papanicolaou staining), and that pathology reporting time may be reduced by up to 20 min per case.…”
Section: Results Of Pico Questionmentioning
confidence: 99%
“…For definitive analysis, often a second slide is fixed for Papanicolaou staining. One study compared ROSE performed with Wright-Giemsa staining versus ROSE with Papanicolaou staining and did not find a significant difference in the yield [44]. …”
Section: Results Of Pico Questionmentioning
confidence: 99%
“…Most studies have used Diff Quik stain, TB and ultra-fast Pap for the purpose of ROSE 5,7,8,10,11 , and very few studies comparing at least two rapid stains are available in the literature. 15 In our study, we have found rapid pap (RP) to be the best stain for ROSE, when only the quality of stain and morphological details are taken into consideration.…”
Section: Whomentioning
confidence: 89%
“…Different staining methods used in the preparation of lymph node TBNA specimens are associated with varying sensitivity [29][30][31], suggesting the important need to examine the optimal staining method for ROSE on brushings in future studies.…”
Section: Limitationsmentioning
confidence: 99%